2021
DOI: 10.1177/10556656211057361
|View full text |Cite
|
Sign up to set email alerts
|

Nonsedated Magnetic Resonance Imaging for Visualization of the Velopharynx in the Pediatric Population

Abstract: Background Non-sedated MRI is gaining traction in clinical settings for visualization of the velopharynx in children with velopharyngeal insufficiency. However, the behavioral adaptation and training aspects that are essential for successful pediatric MRI have received limited attention. Solution We outline a program of behavioral modifications combined with patient education and provider training that has led to high success rates for non-sedated velopharyngeal MRI in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…To accomplish this, many studies have reported child-friendly MRI protocols that assist with successful, nonsedated image acquisition for children with cleft/craniofacial conditions. 11,19,34 These perceived barriers for velopharyngeal imaging continue to be consistent with past reports. Witt et al 9 reported on the evolution of velopharyngeal imaging, including the early applications of MRI for this population.…”
Section: Barriers To Clinical Translationsupporting
confidence: 86%
See 4 more Smart Citations
“…To accomplish this, many studies have reported child-friendly MRI protocols that assist with successful, nonsedated image acquisition for children with cleft/craniofacial conditions. 11,19,34 These perceived barriers for velopharyngeal imaging continue to be consistent with past reports. Witt et al 9 reported on the evolution of velopharyngeal imaging, including the early applications of MRI for this population.…”
Section: Barriers To Clinical Translationsupporting
confidence: 86%
“…To accomplish this, many studies have reported child-friendly MRI protocols that assist with successful, nonsedated image acquisition for children with cleft/craniofacial conditions. 11,19,34…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations